Length of left anterior descending coronary artery determines prognosis in acute anterior wall myocardial infarction. Issue 2 (30th April 2014) - Ilia, Reuben; Weinstein, Jean Marc; Wolak, Arik; Gilutz, Harel; Cafri, Carlos
<x xml:space="preserve">Abstract</x> Background The left anterior descending artery (LAD) supplies blood to a large part of the myocardium. However, the amount of myocardium supplied varies depending on the length of the LAD and as a result, occlusion of its proximal portion may influence outcome. We investigated the prognosis of patients with anterior wall myocardial infarction as the initial presentation of coronary disease who underwent primary percutaneous coronary intervention (PPCI) in our institution due to isolated proximal LAD occlusion. Methods We retrospectively analyzed all patients that underwent PPCI in our institution from 2002 to June 2012. The individuals who fulfilled the above criteria constituted the study group. We recorded demographic, clinical, and angiographic data as well as mortality during the study period. Results Of 2, 532 patients undergoing PPCI, 196 had isolated proximal LAD occlusion. In 112 of them (57%), the LAD wrapped around the apex (group A) and in the remaining 84 (43%), the LAD terminated at or before the apex (group B). At univariate analysis, patients in group A were found to be older (P = 0.04). Over the study period, 28% of patients in group A died in comparison to 2.4% in group B (P < 0.01). When differentiating between cardiac and non‐cardiac death, both were also significantly higher in group A (P < 0.01). At multivariate analysis, the strongest predictor of death was long LAD versus shorter LAD (HR 9.1, 95% CI 1.1–76, P = 0.04). Conclusion Wrap‐around LAD is a strong predictor of prognosis in patients with anterior wall MI undergoing PPCI to isolated proximal LAD occlusion. In addition, those with a shorter LAD have an excellent prognosis. © 2013 Wiley Periodicals, Inc.